0054 Circadian Measures Are Not Phase Delayed in Bipolar Spectrum Disorder in a 20-Day Naturalistic Ecological Momentary Assessment Study. (27th April 2018) - Goel, N; Titone, M K; Ng, T H; Dennis, L E; Alloy, L B
Abstract: Introduction: Prior work demonstrates circadian rhythm disruptions of sleep/wake, activity, hormones, and melatonin in individuals with bipolar spectrum disorder (BSDs). Such disruptions may be a key mechanism underlying neurobiological vulnerability to BSDs. Methods: 150 adults (ages 18–27; mean age ± SD, 21.9 ± 2.1y; 88 women), with high reward sensitivity and a BSD (n = 43), at-risk individuals with high reward sensitivity but no BSD (n = 64), and low-risk individuals with moderate reward sensitivity and no BSD (n = 43) participated in a 20-day naturalistic Ecological Momentary Assessment (EMA) study. The EMA study involved 3 phases: 1. Baseline; 2. Goal striving and 3. Goal/reward outcome; salivary dim light melatonin onset (DLMO) was assessed as a circadian phase marker in each phase. The Morningness-Eveningness Questionnaire (MEQ) assessed chronotype, iButtons measured skin temperature continuously, and wrist actiwatches measured sleep-wake cycles. Multilevel linear models and Pearson's correlations were used for statistical analysis. Results: In our large sample, MEQ scores, DLMOs, skin temperature maximum acrophases and actigraphic sleep midpoints were not significantly different across the three groups at baseline (all Ps>0.05). Notably, throughout the study, these variables showed the expected phase relationships, whereby MEQ was negatively correlated with DLMO (r= -0.562, p<0.05) and DLMO-sleep onset phase angle was positively correlated with skin temperature maximum acrophase (r=0.577, p<0.001), thus validating our circadian measures in a naturalistic EMA design. Conclusion: Our results show for the first time that BSD, individuals at-risk for BSD, and low-risk individuals did not differ across multiple objective circadian markers in a naturalistic EMA study. We contend that reported delays in circadian rhythms in BSD may emerge with greater bipolar severity (e.g., bipolar I disorder), after multiple episodes, and/or with increasing age, among other factors. Our results are relevant for the treatment of BSDs using chronotherapeutic modalities such as light and/or sleep deprivation. Support (If Any): This work was supported by NIH R01 MH102310.